The Industrialization and Commodification of Shalawatan Tradition: Study on the Pekalongan Az-Zahir Assembly - Mohammad Zuhurul Fuad; Sujadi Sujadi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This study aims to observe the phenomenon of reciting shalawat in the Pekalongan Az-Zahir Assembly. Shalawat, which was previously a private domain with a worship value, has gradually changed into an activity with a profit value. This qualitative study employs a socio-cultural approach associated with digital media. Continuing the research on the tradition of reciting shalawat in existing research, most of the existing themes only touch on the aspect of the influence of the shalawat tradition on people's behavior and also increase their love for their homeland. The commodification of shalawat in the Az-Zahir group is reviewed through three aspects: content commodification, audience commodification, and worker commodification. It can be understood that the relationship between the religiosity of commodities and the commodification of religion is complex and interdependent. Commodities are traded goods or services, while religion is a belief system that regulates human relations with God or a higher power. Although originating from different domains, both often influence and shape each other.